Demonstratives, definiteness effects and the type-token distinction - Bosque, Ignacio (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2021)
Definiteness effects have been attested in the literature for some DPs complementing HAVE (= English have and their counterparts in other languages). In this paper, which focuses on English and Spanish, demonstrative DPs are shown to be affected by the type-token distinction in HAVE contexts: the internal argument of HAVE receives a type reading in these cases and rejects a token interpretation. The “type restriction on demonstrative DPs” (TRD) is shown to follow from the need for narrow focus NPs complementing HAVE to receive a hearer-new reading, a well-known property of presentational structures. Type readings of demonstrative DPs are shown to meet this condition. Apparent exceptions to the TRD effect include (i) DPs in so-called “remainder contexts”; (ii) structures in which the relevant DP is the subject of a small clause (sometimes with a non-overt predicate); and (iii) structures containing a number of anti-assertive operators. The contexts in (i) are shown to be hearer-new, in spite of being definite. Those in (ii) and (iii) provide DPs which escape the narrow focus interpretation that gives ride to this variety of the definiteness effect.